An Entrepreneurial Leadership Workshop for Business Actors in Malang City - Armanu, Armanu; Aryati, Ana Sofia; Fasieh , Muhammad Islam Fajrul; Makhmut, Khalilah Daud Isaac (Journal of Interdisciplinary Socio-Economic and Community Study, 2024)
Organisational development is faced with a very dynamic industrial environment such as globalization, rapid increase and development of market and customer needs and demands, digitalisation in every aspect and unexpected events that greatly impact the company. One of the abilities that must be possessed by business actors is entrepreneurial leadership. For the problems faced, some of the solutions offered by the Service Team include changing the mindset of business actors by providing insight or understanding of entrepreneurial values so as to build awareness of the importance of marketing aspects in developing a business. The implementation method is carried out through training activities for small and medium enterprises in Malang City. Entrepreneurial Leadership Training is a program specifically designed to guide and equip participants with the skills, knowledge, and mentality needed to become successful and innovative leaders in the business world. Based on the data obtained from the questionnaire, it shows that the training organisers provide a valuable platform to explore participants' views, thoughts and experiences related to the training they have attended. Through group discussions, participants share knowledge with conveys information, understanding, or experience they have to other people or other groups with the aim of providing benefits and expanding mutual understanding. Future research is expected to include a larger sample to get a broader picture. In addition, it can compare the results of various trainings in order to provide insight into the most effective way to improve the skills of small and medium business actors.